GAMBARAN KADAR SGOT DAN SGPT PADA PETANI YANG MENGGUNAKAN PESTISIDA DI DESA LOA JANAN ULU - Handa Nofianti Rosadi (Akademi Kesehatan John Paul II Pekanbaru, 2023)
ABSTRACT Indonesia is an agricultural country where the agricultural sector is one of the main sources of the economy. However, farmers are worried about pest attacks, so they choose to use pesticides in order to increase agricultural yields. Therefore, in Indonesia, many farmers use pesticides, especially in East Kalimantan, precisely in the village of Loa Janan Ulu. The use of pesticides that violate the rules can endanger health, one of which is liver damage. Examination of SGOT (Serum Glutamic Oxoloacetic Transminase) and SGPT (Serum Glutamic Pyruvic Transminase) levels is one of the markers of liver damage, therefore this study aims to determine the average levels of SGOT and SGPT and the percentage of SGOT and SGPT levels that exceed the normal rate in farmers who use pesticides. The type of research used is descriptive with purposive sampling technique where the number of samples is 37 people. Based on the results, the highest average SGOT levels are at the age of 30-50 years (56 U/L) and work duration >10 years (55 U/L). While the highest average SGPT levels are aged 30-50 years (40 U/L) and have worked >10 years (39 U/L) and the percentage of SGOT levels is 95% and SGPT levels are 46% which exceeds the normal rate. It can be concluded that the average levels of SGOT and SGPT are highest at the age of 30-50 years and have worked for >10 years with a higher percentage of SGOT levels that exceed the normal rate than SGPT. Keywords: Fermers, Pesticide, SGOT, SGPT